Emerging directions of cognitive aging with HIV: practice and policy implications for social work. Issue 5 (4th July 2022) - Vance, David E.; Lee, Yookyong; Batey, David Scott; Li, Wei; Chapman Lambert, Crystal; Nakkina, Sai Rashmi; Anderson, Joseph N.; Triebel, Kristen; Byun, Jun Y.; Fazeli, Pariya L.
ABSTRACT: Cognitive impairments have been endemic to the HIV epidemic since its beginning and persist to this day. These impairments are attributed to HIV-induced neuroinflammation, the long-term effects of combination antiretroviral therapy, lifestyle factors (e.g., sedentary behavior, substance use), neuro-comorbidities (e.g., depression), age-associated comorbidities (e.g., heart disease, hypertension), and others causes. Normal aging and lifestyle also contribute to the development of cognitive impairment. Regardless of the etiology, such cognitive impairments interfere with HIV care (e.g., medication adherence) and everyday functioning (e.g., driving safely, financial management). With more than half of people with HIV (PWH) 50 years and older, and ~45% of all PWH meeting the criteria for HIV-Associated Neurocognitive Disorder (HAND), those aging PWH are more vulnerable for developing cognitive impairment. This article provides an update to a social work model to identify and monitor PWH for cognitive impairment. Within this update, the state of the science on protecting brain health and cognitive reserve within the context of neuroHIV is also presented. From this, implications for practice and policy to promote successful cognitive functioning in older PWH are provided.